Induction of Stem‐Cell‐Derived Functional Neurons by NanoScript‐Based Gene Repression. (10th September 2015) - Patel, Sahishnu; Chueng, Sy‐Tsong Dean; Yin, Perry T.; Dardir, Kholud; Song, Zhichao; Pasquale, Nicholas; Kwan, Kelvin; Sugiyama, Hiroshi; Lee, Ki‐Bum
Abstract Even though gene repression is a powerful approach to exogenously regulate cellular behavior, developing a platform to effectively repress targeted genes, especially for stem‐cell applications, remains elusive. Herein, we introduce a nanomaterial‐based platform that is capable of mimicking the function of transcription repressor proteins to downregulate gene expression at the transcriptional level for enhancing stem‐cell differentiation. We developed the "NanoScript" platform by integrating multiple gene repression molecules with a nanoparticle. First, we show a proof‐of‐concept demonstration using a GFP‐specific NanoScript to knockdown GFP expression in neural stem cells (NSCs‐GFP). Then, we show that a Sox9‐specific NanoScript can repress Sox9 expression to initiate enhanced differentiation of NSCs into functional neurons. Overall, the tunable properties and gene‐knockdown capabilities of NanoScript enables its utilization for gene‐repression applications in stem cell biology.